Persepsi Pelaku Bisnis UMKM Terhadap Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah Pada UMKM Industri Konveksi Desa Botoran, Tulungagung - Mutiara Rachma Ardhiani (INVENTORY: JURNAL AKUNTANSI, 2021)
This study aims to determine and analyze the perceptions of SMEs business actors in the convection industry in Botoran Village, Tulungagung on SAK EMKM. Documentation, observation, and interview techniques were used to collect data. Furthermore, interactive models of analysis are used to analyze the data. The results of the study found that the SMEs in the convection industry in Botoran Village, Tulungagung had not entirely implemented SAK EMKM so that the resulting financial reports were still not fair and not comparative.